Making Do: Women, Family, and Home in Montreal during the Great Depression - Baillargeon, Denyse (Wilfrid Laurier University Press, 1999)
Keywords: Crise; Famille; Femmes

Praticiennes et patientes. Les femmes et la santé dans l'historiographie québécoise - Baillargeon, Denyse (Revue d'histoire de l'Amérique française, 1999)
Keywords: Femmes; Médecine

Les cours d'instruction civique de la Fédération Nationale Saint-Jean-Baptiste. Une voie d'accès à la citoyenneté politique pour les femmes du Québec - Cohen, Yolande; Maillé, Chantal (Recherches féministes, 1999)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

De Jeanne D'Arc à Madeleine de Verchères: la femme guerrière dans la société d'Ancien Régime - Gervais, Diane; Lusignan, Serge (Revue d'histoire de l'Amérique française, 1999)
Keywords: Combat; Femmes; Forts

Writing Bodies: Modern Dance, Gender, and Jewish Identity in New York and Montreal, 1930 to 1960 - Hardt, Yvonne (Université Concordia, 1999)
Keywords: Danse; Juifs

La philanthropie et la violence maritale. Le cas de la Montreal Society for the Protection of Women and Children et de la Woman's Christian Temperance Union of the Province of Quebec - Hébert, Fernand (Université du Québec à Montréal, 1999)
Keywords: Enfants; Famille; Femmes; Philanthropie

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
Keywords: Femmes; Fédération nationale Saint-Jean-Baptiste

De la clandestinité à l'affirmation: pour une histoire de la communauté gaie montréalaise - Higgins, Ross (Comeau & Nadeau, 1999)

Femmes et organisations environnementales, l'activisme au féminin: étude de cas - Laloux, Aurélie (Université du Québec à Montréal, 1999)
Keywords: Femmes; Groupes populaires

La structure spatiale des déplacements pendulaires des femmes et des hommes dans la région de Montréal - Lemelin, André; Gatignol, Agnès (Cahiers de géographie du Québec, 1999)

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

The Homeless, the Whore, the Drunkard, and the Disorderly: Contours of Female Vagrancy in the Montreal Courts, 1810-1842 - Poutanen, Mary Anne (Gendered Pasts: Historical Essays in Femininity and Masculinity in Canada, 1999)
Keywords: Délinquance; Femmes; Itinérance; Prostitution

Barbe de Boullougne ou l’ascension d’une femme dans la Nouvelle-France du XVIIe siècle - Vachon, Louise (Université de Montréal, 1999)
Keywords: Confrérie de la Sainte-Famille; Confréries